Analysis of Student Economic Conditions in Choosing Career Plans from the Perspective of the Guidance Counseling Industry, Central Kalimantan, Indonesia - Alia Rosa Kludia; Sabila Sabila; Melani Putri; Nur Sabila; Karyanti Karyanti; Asep Solikin; M. Fatchurrahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: Socioeconomic conditions are contextual factors that shape the selection of career plans, especially for prospective workers in developing regions such as Central Kalimantan. Aim: This study aims to describe the economic conditions of the respondents and to analyze their implications for career choice in the context of Industrial Guidance and Counseling. Method: The research uses a quantitative, descriptive design. Data was collected through questionnaires and analyzed descriptively using frequency and percentage distributions. Results and Discussions: The results of the study showed that the economic condition of the respondents was dominated by the medium economic category, followed by the medium, low, and high economic categories. These findings indicate that the majority of respondents are in a transition phase towards economic independence, which affects the direction and realism of their career plans. The discussion of the results confirmed that economic conditions do not stand alone, but interact with psychosocial factors and the industrial environment. Conclusion: The study emphasizes the importance of industrial guidance and counseling in helping individuals develop adaptive, sustainable career plans. Therefore, it is recommended to develop industrial Guidance and counseling services based on socioeconomic conditions to support the selection of a fair career plan.